Canon and Curation: What does the Completion of RPP Mean for North American Students of Theology, Church History, and Philosophy? - Saler, Robert C. (Bulletin for the study of religion, 2015)
This paper offers commentary on the relative merits of the RPP in the specific areas of theology, church history, and philosophy. The encyclopedia's treatment of these themes, while largely adequate, raises substantial meta-questions within the discipline about how notions of "canon" function with authority in a time of unprecedented disciplinary fragmentation, particularly within theology itself.